IOT-Enhanced MPPT Charge Controllers for Sustainable Energy - HASHIM, HAIKAL; Farahiyah Mustafa; Lam Hong Yin (Progress in Engineering Application and Technology, 2024)
Solar energy, as a sustainable and eco-friendly source from the sun, faces challenges like intermittent power generation and storage limitations. Integrating batteries resolves the issue of non-storability in standalone PV systems. The Maximum Power Point Tracking (MPPT) technology in solar charge controllers maximize the maximum power point (MPP) maximizes solar panel power output using the Perturb and Observe (P&O) and Incremental Conductivity (IC) method, enhancing efficiency and extending battery life. Components like MPPT, Arduino Nano, LCD display, and Wi-Fi module ensure optimized energy harvesting and battery charging. Overall, utilizing an MPPT solar charge controller with monitoring offers a reliable way to efficiently charge batteries with solar power, showcasing the effectiveness of solar energy in powering and charging systems.